A Review of Michael Tomz's Reputation and International Cooperation: Sovereign Debt across Three Centuries - Gersovitz, Mark (Journal of Economic Literature, 2009)
Repudiation and expropriation pose obstacles to the international mobility of capital and thereby to efficient international allocation of resources. Tomz discusses the determinants of lending in the face of the threat of repudiation. Using history, he argues that debtor countries have sought a reputation for compliance with loan agreements to access future loans and that military or trade sanctions have been unimportant in sustaining lending. He discusses when and why banks have been more active as lenders relative to bondholders. This article situates Tomz's concerns in the broad themes of thought on obstacles to capital mobility and evaluates his arguments.